New MCEQLS AHP method for evaluating quality of learning scenarios - Kurilovas, Eugenijus; Zilinskienė, Inga (Technological and Economic Development of Economy, 2013)
The aim of the paper is to present a new MCEQLS AHP method for the expert evaluation of quality of learning scenarios. A special attention is paid to suitability of scenarios to particular learner groups (styles). Solution of learning scenarios quality evaluation and optimisation problem could help educational institutions to select suitable scenarios for particular learning styles. The research results will be implemented in iTEC – a four-year, largest pan-European e-learning R&D project focused on the design of the future classroom funded by 7th Framework Programme. A novel method of consecutive triple application of AHP is explored in more detail. Suitability of several iTEC scenarios to particular learner groups is also analysed in the paper. A number of multiple criteria decision analysis principles are applied to create a comprehensive quality model (criteria tree) for evaluating quality of scenarios. Several optimisation methods are explored and applied to optimise learning scenarios in conformity with particular learning style. Several practical examples of iTEC learning scenarios alternatives have been evaluated against the proposed MCEQLS AHP method. The research results have shown that the proposed MCEQLS AHP method is quite objective, exact and simple to use for selecting qualitative scenarios alternatives for particular learner groups.